Elementary physical educators’ positioning in teaching English language learners - Sato, Takahiro; Walton-Fisette, Jennifer; Kim, Insook (European physical education review, 2019)
Public schools in the United States (US) have become more linguistically diverse. With the rise of English as a global language, English Language Learners (ELLs) experience “transnationalism”, which requires them to gain a critical and reflective knowledge of diverse cultures and the valuing of a new language and culture. Many teachers do not recognize the importance of language as a tool for teaching academic subjects. Teachers struggle to shape and guide conversations using language to help ELLs further their development. The purpose of this study was to explore elementary physical education (PE) teachers’ experiences with teaching ELLs. Based on positioning theory, this study employed an interpretive case study research design. Six PE teachers volunteered to participate in the study. Data were collected from a survey questionnaire, face-to-face interviews and follow-up e-mails. Three major interrelated and complex themes emerged from the data analysis. These recurrent themes were (a) race and cultural-based stereotype, (b) social inclusion and communication challenges, and (c) PE teachers’ learning experiences. Although each of the PE teachers expressed the view that there were challenges in working with ELLs, they believed that they should implement effective pedagogical methods (inclusive pedagogy), address social justice and diversity issues of ELLs, and develop a positive learning atmosphere for all students.